The Typologization Problem of Free Time - Mitrikas, Alfonsas Algimantas (Problemos, 1975)
In this part of the paper (for the beginning see Problemos 15, 1975) the typologization problem of spending free time (FT) is considered from the viewpoint of dynamics of processes of FT in the socialist society. Raising the question of “discovering” the types of spending FT. which could be taken as ontological constructs, reflecting real processes of spending FT, the author shows the role of both the theoretical and the empirical investigation in this sphere. The static and dynamic stability of the types is discussed and the conclusion is drawn that stability of a type is immanent to the existence of the type.